Isolated Vertical Ophtalmoplegia and Mydriasis Due to Bilateral Midbrain Infarction - Budak, F.; Aydin, E.; Kockaya, A.; Ozkara, B. (Journal of Neurology and Epidemiology, 2017)
Partial fascicular oculomotor palsy, the combination of bilateral midriasis with loss of vertical gaze movements, is rarely a consequence of midbrain infarction. We describe a patient with acute ischemic infarcts involving both upper most part of the midbrain, presenting with marked vertical gaze palsy and mydriasis bilaterally as the only neurological abnormality. These features are suggestive of partial fascicular oculomotor palsies involving the pupil, inferior rectus(IR), superior rectus(SR), inferior oblique(IO) muscles and sparing medial rectus(ML), levator palpebrae(LP) muscles. These neuro-ophthalmological and radiological findings in our case support the model that the fibers to medial rectus and levator palpebrae muscles might be located in the more caudal portion of the oculomotor fascicles.